A remarkable new genus of Protosmylinae (Neuroptera: Osmylidae) from late Eocene Florissant, Colorado - Makarkin, Vladimir N. (Zootaxa, 2017)
Pseudosmylidia relicta gen. et sp. nov. (Neuroptera: Osmylidae) is described from the late Eocene of Florissant (U.S.A., Colorado). It is assigned to the subfamily Protosmylinae based on the presence of two venational features characteristic of the subfamily: most crossveins in the radial to intramedial spaces of the forewing are arranged in four gradate series, and CuP is short and simple or forked only once in the hind wing. This genus is remarkable by CuP in the forewing bearing few pectinate branches. This is the only genus of extant and Cenozoic fossil Osmylidae in which this plesiomorphic condition is retained.